2015
DOI: 10.1111/1750-3841.12844
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antifungal Peptides Produced by Leuconostoc mesenteroides DU15 Effectively Inhibit Growth of Aspergillus niger

Abstract: The ability of Leuconostoc mesenteroides DU15 to produce antifungal peptides that inhibit growth of Aspergillus niger was evaluated under optimum growth conditions of 30 °C for 48 h. The cell-free supernatant showed inhibitory activity against A. niger. Five novel peptides were isolated with the sequences GPFPL, YVPLF, LLHGVPLP, GPFPLEMTLGPT, and TVYPFPGPL as identified by de novo sequencing using PEAKS 6 software. Peptide LLHGVPLP was the only positively charged (cationic peptides) and peptide GPFPLEMTLGPT ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…To assess the antifungal activity of WSE and the fractions (WSE 30 , permeate <30 kDa; WSE 10, permeate <10 kDa) the micro-titer plate assay, as previously proposed by Muhialdin et al [40], was used, with some modifications [18]. After growth for 7 days on PDA plates, conidia of P. roqueforti DPPMAF1, used as an indicator, were harvested in sterile water containing 0.05% (v/v) Tween 80.…”
Section: Micro-titer Plate Assaymentioning
confidence: 99%
“…To assess the antifungal activity of WSE and the fractions (WSE 30 , permeate <30 kDa; WSE 10, permeate <10 kDa) the micro-titer plate assay, as previously proposed by Muhialdin et al [40], was used, with some modifications [18]. After growth for 7 days on PDA plates, conidia of P. roqueforti DPPMAF1, used as an indicator, were harvested in sterile water containing 0.05% (v/v) Tween 80.…”
Section: Micro-titer Plate Assaymentioning
confidence: 99%
“…Furthermore, Leuconostoc mesenteroides strains have a wide spectrum of antifungal activity against Aspergillus fumigatus, Aspergillus niger, Penicillium roqueforti, and some other common spoilage fungi. Thus, Leuconostoc mesenteroides has the potential to become a biopreservative in food industry (Lee and Chang, 2016;Muhialdin et al, 2015). also isolated a new phenyl lactic acid derivative and some known metabolites from the culture medium of Leuconostoc mesenteroides that showed high radical-scavenging activities, suggesting that this species could produce antioxidative compounds.…”
Section: Resultsmentioning
confidence: 98%
“…In the case of chopea-thionin II, an initial interaction of the peptide with fungal cells was reported (Schmidt et al 2019), with consequent membrane permeabilization and cell lysis or, as demonstrated here for ApoB-derived peptides, with subsequent internalization into fungal swollen spores or initial hyphae. Peptides isolated from Leuconostoc mesenteroides DU15 were, instead, found to be able to affect by 50% the growth of A. niger by causing significant morphological changes of branched mycelium, as evidenced by scanning electron microscopy analyses, and a reduction in the number of fungus cells (Muhialdin et al 2015). Based on the obtained results, ApoB-derived peptides are able to exert strong effects on A. niger N402, and, even more importantly, they possess additional properties with respect to previously identified antifungal peptides, such as lower MFC values and the ability to affect different stages of fungal growth.…”
Section: Apob-derived Peptides Affect a Niger N402 Metabolic Activitymentioning
confidence: 95%